Analisis Penurunan Jatuh Tegangan dan Losses akibat Sambungan Deret dengan Penambahan Jaringan Tegangan Rendah serta Rekonfigurasi Sambungan Rumah - Bagas Septian Pamungkas; Amani Darma Tarigan; Muhammad Fahreza (Jurnal Serambi Engineering, 2024)
The Service Entrance (SE) is the end of the power distribution system to the customer, from where the quality of the voltage distributed by PT PLN (Persero) can be seen. At PT PLN Rayon Pedan, there are many report from customers as well as inspection teams and technical services about the voltage drop in customers' homes. One of them is from Dukuh Nanggulan, Cawas Klaten. After being inspected by the technical department of PLN Rayon Pedan, there were many house connections that did not comply with PLN Standard 56-1 in 1993. The house connection can cause voltage drop and carrier loss. According to the measurement at the time of the peak load, the voltage at the end of the line dropped by 178.21 volts. This violates the tolerance limits specified by PLN in SPLN 1 1995 regarding the standard voltage, which is -10% for the lower limit or as much as 198 volts from the nominal voltage standard PLN 220 V. To overcome the voltage drop and loss caused by the service entrance, the authors of the series perform improved planning by adding new low voltage networks as well are configuring old service entrancesusing ETAP 12.6.0 software to compare results before and after reconfiguration of the service entrance.